Décalage et déséquilibre dans la peinture contemporaine de la Nouvelle-Orléans - Hélène GAILLARD (E-REA)
This paper examines the aesthetics of imbalance in contemporary painting representing New Orleans. The depiction of the city as an unsteady, dynamic, marginal entity corresponds to the wavy topography of the town but is also the visual translation of its musical heritage. The phenomenon increased after Katrina and painters such as James Michalopoulos, Terrance Osborne and Phil Sandusky have tried to find new ways to represent and magnify New Orleans’s inherent off-centered quality.